Development of SIRT1 siRNA-carrying liposomes for treatment of prostate cancer - Oner-Bozkurt, Ezgi (My University, 2020)
Sirtuin 1 (SIRT1) is a histone deacetylase (HDAC) from Sirtuin family and high expression of it induces activation of DNA repairing factors eventually leading either tumor suppression or tumor development in cellular context-dependent manner. Since most of the chemotherapeutics induce apoptosis by creating DNA damage in tumor cells and further SIRT1-activated repair of the chemotherapeutic-induced DNA damage results in decreased apoptosis, inhibition of SIRT1 is a promising strategy both in anticancer therapy and preventing chemotherapy resistance. High expression level of SIRT1 in prostate cancer level has been also reported in many cases and it has been confirmed in our context by showing the higher protein levels of SIRT1 in prostate cancer cell lines than normal prostate epithelium cells. As, gene silencing of oncogenes via RNA interference technology is a recent approach in cancer therapy, in this study, siRNA carrying liposomal formulations composed of N-[1-(2,3-dioleyloxy)propyl]-N,N,N-trimethylammonium chloride (DOTMA) as cationic lipid have been formulated by freeze drying method for SIRT1 inhibition. In addition to characterization of the liposomes, their efficiency on SIRT1 silencing has been shown both on mRNA and protein levels on prostate cancer cell lines LNCaP, Du145, and PC-3. It has also been determined that each liposomal formulation has different levels of efficiency on each cell line so it has been achieved to develop an appropriate nucleic acid delivery formulation for SIRT1 silencing for different metastatic prostate cancer types.
BioTurkey International Biotechnology Congress
Keywords: Liposome; SIRT1; nucleic acid delivery; prostate cancer; Cancer; Nanoscience & Materials; Drug Delivery Systems; Gene therapy; Nano Biotechnology; NanoMedicine; Nanotechnology; Prostate cancer